Teori Demokrasi dalam Wacana Ketatanegaraan Perspektif Pemikiran Hans Kelsen - HM. Thalhah (Jurnal Hukum IUS QUIA IUSTUM, 2009)
In Hans Kelsen opinion, one of the essences of democracy is the possibility for compromising various aspirations with regard to the foundation of a state. The principle of compromise is the settlement of a conflict via certain procedure which is not fully in favor of a party and ignoring the rests. By this compromise, democracy performs as an approach in the process of achieving the hope perfectly.Keywords: the theory of democracy, aspiration of the majority, aspiration of the minority, compromise.